A tale of 19 testes. Issue 2 (March 2014) - Hackett, Geoffrey
Abstract Professor Hackett presents the case histories of ten doctors, providing a personal insight into the problems caused by low testosterone levels and highlighting health professionals' reluctance to consult with sexual issues in primary care. Culley Carson adds a urologist's comment at the end. Copyright © 2014 John Wiley & Sons